Studies of polylactide/zinc oxide nanocomposites: influence of surface treatment on zinc oxide antibacterial activities in textile nanocomposites. Issue 17 (24th January 2015) - Doumbia, Awa Soronfé; Vezin, Hervé; Ferreira, Manuela; Campagne, Christine; Devaux, Eric
ABSTRACT: Polylactide (PLA)/zinc oxide (ZnO) nanocomposite filaments were produced with a melt‐spinning process, with the aim of obtaining antibacterial textiles. ZnO, an inorganic antibacterial nanofiller, is used to impart antibacterial properties to PLA. These nanoparticles suit the melt‐spinning process because of their high thermal stability and low granulometry. Generally, metallic oxides (e.g., ZnO) are used to recycle PLA via catalyzed unzipping depolymerization. In this study, we used different ways to finely disperse ZnO in PLA and produce filaments with a minimum degradation of the thermal and mechanical properties. Optimized antibacterial properties were obtained with a fabric containing ZnO with specific surface treatments. The reasons for this better antibacterial activity, related to the study of the antibacterial mechanism of ZnO, were investigated with different characterization techniques [X‐ray, electron probe microanalysis, inductively coupled plasma mass spectrometry, and electron paramagnetic resonance (EPR)]. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2015, 132, 41776. Abstract :